TikTok Application on Achievement and Learning Motivation at Influence Colleges - Nur Azlin Putri; Kamaluddin Kamaluddin; Amrina Amrina (Yayasan Adra Karima Hubbi, 2023)
TikTok is an application that many people love; Tiktok contains many information and videos that attract its users' attention—starting from children, teenagers, adults, and even the elderly. Because this Tiktok application can be used in any circle, this Tiktok application is effortless to access via cellphones or other devices such as laptops, tablets, and computers. The use of the Tiktok application is the largest in the world because Tiktok is very much in demand, and the way to use it is effortless, so that most people can use this Tiktok application. This research aims to discuss problems in using the Tiktok application and its role in life. In this case, it also discusses the impact of the Tiktok application, both positive and negative effects, and its influence on achievement and motivation to study in tertiary institutions. Researchers use the quantitative method, carried out by way of researchers distributing Google forms to students and the community. Then the researchers also conducted several interviews directly with students at UIN Mahmud Yunus Batusangkar. The results of the study show that the majority think that the use of the Tiktok application in college is very much in demand and has many positive values ??contained in it. The drawbacks of this research are that not many interviews were conducted with other parties, and the researchers only focused on students. Therefore, further research is expected to be more complete.